AN ERROR ANALYSIS OF USING SIMPLE PRESENT TENSE IN WRITING DESCRIPTIVE - Abdi Putra Arianto Simanjuntak; Aryo Hans Tobing; Desi Simbolon; Tumiar Silaban (Journal of English Language Teaching, Literatures, Applied Linguistic (JELTLAL), 2025)
This Descriptive text is a type of writing that explains or illustrates people, places, and objects by focusing on their physical characteristics or appearances.This study analyzes students’ grammatical errors in using the simple present tense in descriptive texts. Conducted on 24 second-semester English Education students at HKBP Nommensen University Medan, the research used a qualitative descriptive method and surface strategy taxonomy (Dulay et al., 1982) to classify errors into omission, addition, misinformation, and misordering. The population of this research included all second-semester students of the English Education Study Program at HKBP Nommensen University Medan during the academic year of the study. These students had completed Writing I and were enrolled in Writing II, which covers the use of grammatical structures such as the simple present tense in descriptive writing. Using purposive sampling, one class (Class B) was selected, consisting of 24 students who met the criteria and were deemed suitable for analyzing grammatical errors. The primary instrument was a supervised writing task, where students wrote a five-paragraph (200–300 words) descriptive text about a person, place, or thing within 60 minutes. Their texts were analyzed using the Surface Strategy Taxonomy (Dulay, Burt, & Krashen, 1982), which classifies errors into omission, addition, misinformation, and misordering. For data validity, two grammar experts assisted in reviewing and confirming the identified errors through triangulation. From 263 simple present tense usages, 141 (53.61%) were incorrect. The most frequent error was omission (40%), followed by addition (29%), misformation (18%), and misordering (13%). These findings indicate that students still face difficulties in mastering simple present tense, especially in forming grammatically complete sentences.